Do increases in subsidized housing reduce the incidence of homelessness? Vidence from the low-income housing tax credit - Osborne Jackson; Laura Kawano (Federal Reserve Bank of Boston, 2015)
We examine the impact of subsidized housing on homelessness using the Low-Income Housing Tax Credit (LIHTC), the largest place-based housing program in the United States. To generate quasi-experimental variation in housing placements, we exploit a discontinuous increase in the amount of tax credits available to projects placed in certain high-poverty neighborhoods. Using data from the U.S. Census and HUD, we find that LIHTC project installation has no significant impact on neighborhood homelessness but does significantly reduce county-level homelessness. Our analysis suggests that the mobility of the homeless across neighborhoods helps to explain this result. These findings are consistent with the impacts of place-based policies crossing local boundaries and homeless housing demand that is sensitive to rental prices.
Keywords: H20; H31; I32; R21; R31; 330; low-income housing; tax credits; homelessness; regression discontinuity